Use of Archived Neonatal Bloodspots for Examining Associations between Prenatal Exposure to Potentially Traumatic or Stressful Life Events, Maternal Herpesvirus Infection and Lifetime History of Generalized Anxiety Disorder in Offspring - Simanek, Amanda M.; Uddin, Monica; Yolken, Robert H.; Aiello, Allison E. (Frontiers in Environmental Science, 2016)
Background: Lifetime prevalence of anxiety disorders is over 32% among U.S. adolescents, warranting further investigation into early life risk factors for such conditions. We conducted a pilot study to examine the role that maternal herpesvirus infection may play in the pathway between maternal trauma and stress during pregnancy and offspring generalized anxiety disorder (GAD). Methods: Participants included 69 women in the Detroit Neighborhood Health Study with data on past exposure to 19 potentially traumatic (PTEs) and 9 stressful life events (SLEs). Lifetime history of GAD in the youngest biologic child between 6-17 years old born in Michigan (i.e., index child) of each woman was ascertained via the Diagnostic Interview Schedule for Children, 4th edition, parent version. We obtained written informed consent from participants for retrieval of archived neonatal bloodspot samples corresponding to their index child from the Michigan Neonatal Biobank (MNB) and testing of these samples for markers of maternal herpes simplex virus (HSV)-1 and cytomegalovirus (CMV) seropositivity. Logistic regression was used to examine the association between maternal PTEs or SLEs during pregnancy and offspring GAD. Results: A total of 18.1% and 31.9% of women experienced ≥ 1 PTE or SLE during pregnancy, respectively, and 10.8% of offspring met the criteria for lifetime history of GAD. We obtained maternal consent for retrieval of and tested bloodspot samples corresponding to the index child of 22 women (38%), of which 4.5% and 40.9% were seropositive for HSV-1 and CMV, respectively. We observed positive, although not statistically significant associations between ≥ 1 PTE or SLE during pregnancy and offspring lifetime history of GAD. While a greater proportion of offspring with lifetime history of GAD were born to women seropositive for CMV and HSV-1, compared to those without lifetime history, these differences were not statistically significant and we did not further examine the mediating role of maternal herpesvirus seropositivity in this pathway. Conclusion: Findings from this study support the feasibility of utilizing neonatal bloodspots archived in the MNB to examine the role of herpesviruses as mediators between maternal traumatic or stressful life events during pregnancy and offspring anxiety disorders in larger Michigan cohorts.